2017
DOI: 10.13057/tropdrylands/t010202
|View full text |Cite
|
Sign up to set email alerts
|

Response of some upland rice varieties to drought stress

Abstract: Abstract. Purwanto E, Samanhudi, Yoniar Effendi Y. 2017. Response of some upland rice varieties to drought stress. Trop Drylands 1: [69][70][71][72][73][74][75][76][77]. The study aimed to examine the response of upland rice varieties at germination stage on several PEG (Polyethylene Glycol) 6000 concentration levels and to determine growth characteristics, physiological changes and yield of upland rice varieties under drought stress condition in a pot experiment. The study consisted of two experiments; the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
0
2
0
2
Order By: Relevance
“…Plants will adjust photosynthates partitioning among the organs under drought conditions. Drought stress increases the root-shoot ratio, indicating that photosynthates are partitioned more toward root formation and reduces canopy growth (Purwanto et al 2017).…”
Section: Drought Tolerance Evaluation On the Seedling Stagementioning
confidence: 99%
See 1 more Smart Citation
“…Plants will adjust photosynthates partitioning among the organs under drought conditions. Drought stress increases the root-shoot ratio, indicating that photosynthates are partitioned more toward root formation and reduces canopy growth (Purwanto et al 2017).…”
Section: Drought Tolerance Evaluation On the Seedling Stagementioning
confidence: 99%
“…Drought recovery refers to the plants' capability to resume growth after experiencing the adverse effects of drought stress (Purwanto et al 2017). The plant recovery ability evaluation showed that lines E33-CK1-BP, E38-CK1-BP, CG9-53-1-3, and Salumpikit as a drought-tolerant check variety were categorized as tolerant (Table 10).…”
Section: Drought Tolerance Evaluation On the Seedling Stagementioning
confidence: 99%
“…Dalam kondisi tercekam kekeringan, tinggi tanaman beberapa aksesi sorgum biasanya mengalami penurunan (Widiyono et al, 2020). Hal ini juga sesuai dengan pendapat (Purwanto, Samanhudi, & Effendi, 2017), bahwa peningkatan intensitas cekaman kekeringan mengakibatkan penurunan tinggi tanaman. Penurunan tinggi tanaman yang signifikan mulai terjadi pada kadar air tanah sebesar 50% kapasitas lapang.…”
Section: Gbr 4 Rerata Tinggi Tanaman Sorgum Manis (Cm)unclassified
“…Semakin lama interval waktu penyiraman tampak semakin menurunkan nilai ILD. Hal ini diduga karena respons tanaman terhadap cekaman kekeringan dilakukan dengan menurunkan luas daun untuk mengurangi kehilangan air dari transpirasi (Tourneux et al, 2003 (Purwanto et al, 2017).…”
Section: Hasil Dan Pembahasanunclassified